Mobilizing others: grammar and lexis within larger activities - Taleghani-Nikazm, Carmen Masoomeh; Betz, Emma; Golato, Peter (Studies in language and social interaction, 2020)
Requesting, recruitment, and other ways of mobilizing others to act have garnered much interest in Conversation Analysis and Interactional Linguistics. This volume takes a holistic perspective on the practices that we use to get others to act either with us, or for us. It argues for a more explicit focus on ‘activity’ in unpacking the linguistic and embodied choices we make in designing mobilizing moves. Drawing on studies from a variety of different languages and settings, the collected studies in this volume illustrate how interactants design their turns not only for specific recipients, but also for a specific interactional situation. In doing so, speakers are able to mobilize others’ cooperation, contribution, or assistance in the most appropriate and economical ways. By focusing on ‘situation design’ across languages and settings, this volume provides new insights into the ways in which the ongoing activity, with its attendant participation structures, shapes the design, placement, and understanding of moves which mobilize others to act.